2005
DOI: 10.1007/s00018-005-5433-4
|View full text |Cite
|
Sign up to set email alerts
|

Multiple cAMP-induced signaling cascades regulate prolactin expression in T cells

Abstract: Abstract. Beside its pivotal role in reproduction, the pituitary hormone prolactin (PRL) has been attributed an immunomodulatory function. Here we report that cAMP is an important stimulator of PRL transcription in primary human T lymphocytes. Inhibition of both protein kinase A (PKA) and p38 MAPK partially abrogated cAMPinduced PRL expression. In addition, cAMP-induced phosphorylation of p38 was shown to occur independently of PKA and could be mimicked by a methylated Cell. Mol. Life Sci. 63 (2006) 0092-0099… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 63 publications
0
17
1
Order By: Relevance
“…Our results showed that both T eff and T reg cells constitutively expressed PRL mRNA; this is different from PRL receptor expression, which is only constitutively expressed in T reg cells. In addition, we showed that PRL mRNA expression did not increase in T eff or T reg cells when they were activated with anti-CD3/ CD28; these results differed from a previously published report in which the authors observed an increase in PRL mRNA expression in T cells (Gerlo et al 2006). This difference could be accounted for in several ways.…”
Section: Cd25contrasting
confidence: 99%
“…Our results showed that both T eff and T reg cells constitutively expressed PRL mRNA; this is different from PRL receptor expression, which is only constitutively expressed in T reg cells. In addition, we showed that PRL mRNA expression did not increase in T eff or T reg cells when they were activated with anti-CD3/ CD28; these results differed from a previously published report in which the authors observed an increase in PRL mRNA expression in T cells (Gerlo et al 2006). This difference could be accounted for in several ways.…”
Section: Cd25contrasting
confidence: 99%
“…Epac1 is most abundant in the heart, kidney, blood vessels, adipose tissue, central nervous system, ovary, and uterus (de Rooij et al, 1998;Kawasaki et al, 1998), whereas Epac2 splice variants (Epac2A Biology of the Epac Signalosome and Epac2B) are mostly expressed in the central nervous system (Epac2A), adrenal gland (Epac2B), and pancreas (Epac2A; (de Rooij et al, 1998;Kawasaki et al, 1998;Niimura et al, 2009). Additionally, expression of Epac1 has been found to be present in monocytes, macrophages, B and T lymphocytes, eosinophils, neutrophils, platelets, and in CD34-positive hematopoietic cells (Tiwari et al, 2004;Bryn et al, 2006;Gerlo et al, 2006), whereas Epac2 was undetectable in all studied hematopoietic cell types (Tiwari et al, 2004). Neurite outgrowth and axon regeneration require Epac2 upregulation and Epac1 downregulation in adults (Murray and Shewan, 2008;Murray et al, 2009a).…”
Section: A the Discovery Of Epacmentioning
confidence: 99%
“…This ecto-apyrase activity modulates many of the purinergic signaling processes in which ATP or ADP play a role, and is important for the tonic maintenance of vascular homeostatic properties related to inflammation, coagulation, vasodilation, and barrier function. For instance, CD39 can inhibit platelet activation and maintain vascular fluidity in the complete absence of prostacyclin and nitric oxide as well as regulate immune function and provide protection from both cardiac and cerebral ischemia and reperfusion injuries (1)(2)(3)(4)(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%